KONSEP KURIKULUM MERDEKA DAN INTEGRASI MEDIA PEMBELAJARAN BERBASIS DIGITAL PADA JENJANG SEKOLAH DASAR - Durroh Nasihatul Ummah; Nadlir Nadlir (Universitas Islam Malang, 2023)
The rapid development of technology is a new challenge in the world of education. The paradigm shift in learning practices from only presenting information has shifted to equipping students with the ability to find out, solve problems, digital literacy and creativity. Changes in curriculum policy also result in changes to models, strategies, methods and new learning media. The purpose of this study is 1) to describe the concept of an independent curriculum, 2) find integration of digital-based learning media at the elementary school level. This research uses a descriptive qualitative method with a library research approach or literature study. Data collection was obtained by reviewing various relevant literature. Data analysis through content analysis. The results of the study show 1) The independent learning curriculum concept is the result of the 2013 curriculum evaluation which includes a) Learning is focused on essential material so that there is time to deepen literacy and numeracy competencies, b) Project-based learning for developing skills and strengthening the character of Pancasila student profiles. c) Teachers are given the freedom to make differentiation in learning according to the needs and abilities of students. 2) Integration of digital-based learning media in the independent curriculum is contained in teaching tools in the form of teaching modules, learning objectives flow (ATP), as well as projects to strengthen the Pancasila profile. This digital-based learning media is also available on a digital platform provided by the Ministry of Research, Technology and Higher Education and can be developed by teachers according to students' needs.